Processed Utilization of Balakka Fruit (Phyllanthus Emblica) in Rimba Soping Village, Padangsidimpuan District Angkola Julu - Lubis, Rafiqah Amanda (Journal of Saintech Transfer, 2019)
This community service took place in Rimba Soping Village, Padangsidimpuan District Angkola Julu, Padangsidimpuan City. The implementation method used is counseling methods, and training or mentoring. The approach method used is: a) Counseling about the application of the benefits of fruit and vegetables b) Training and mentoring of Balakka fruit processing. Based on the results of the Community Partnership Program (PKM) activities that have been implemented, conclusions can be drawn, namely: 1) Very positive results are obtained from the partners during the activities 2) The transfer of knowledge and information to partners in an effort to use balakka fruit 3) There is added value (value added) from Balakka fruit 4) The high motivation of KWT Rotama in Balakka fruit innovation 5) Reducing capital constraints in starting a business by utilizing available natural products.